(3WQR GdhaG aj aVd Bd GdoeUWais - (3CMeO Rjf GdYGHOjf Hf eMeO Rjf GdYGHOjf Hf eMeO CHh GdMSfs ((3MSf Hf Ydj GdZRGdj s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CWdY ef SeGA GdMbjbI GdoeMeOjI TeSkG hHOQkG s
(3BNQgG (B:s
(3hddeDefjf Gdcd aGfXQ Edjge Edgi HZaQGf haVdc hGSY s
(3hgj efShNI ef fSNI GdeDdas
(3hHChdgG hbajI eDQNI SfI (B1190 (3g` hCNQi SfI (B1194(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B282 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJGQjNs